Sistem Informasi Manajemen Penilaian Kelayakan Mustahik pada Baznas Provinsi Papua - Alam, Sitti Nur; Nurhayati, Siti; Waja, Afgan; Robo, Salahudin; Widiyantoro, M. Riandi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
BAZNAS Papua Province has several stages that must be carried out in the process of distributing Zakat, Infaq and Sadaqah (ZIS) to the mustahiq, one of the stages is mustahiq assessment survey on the field. With a large number of mustahiq being surveyed every day and the eligibility assessing process still be carried out manually utilizing survey form recording, the survey stage of the ZIS distribution process takes a long time. In addition, physical document usage continues to increase every day becomes more susceptible to damaged and loss and requires extensive storage in the archiving process. This study uses a PIECES analysis method as well as system development use a Waterfall method. Furthermore, the Unified Modeling Language (UML) method is used to design the system. The system is built on web-based using the PHP programming language and the MariaDB database. The results of this study are the Management Information System of Mustahiq Eligibility Assessment at BAZNAS Papua Province that is capable of organizing mustahiq data, assessing mustahiq eligibility and minimizing the usage of physical documents in the ZIZ distribution process. The system is built to produce information about mustahiq recommendation that is capable of assist BAZNAS Papua Province to come to a final decision.